The Educational Needs of Family of Patients Discharged from the Intensive Care Units: The Viewpoints of Nurses and the Patients’ Families - Asma Hajalizadeh; Mehdi Ahmadinejad; Mahlagha Dehghan; Mansoor Arab (Critical Care Research and Practice)
Introduction. Thousands of patients are admitted to the intensive care units annually, which are stressful for patients and their families. The discharged patients and their families face different challenges in the caring process of the patients. Objectives. This study aimed to determine the educational needs of the families of patients discharged directly home from the postintensive care units and to compare the views of families and nurses about these needs. Method. This was a cross-sectional study. One hundred forty nurses and 140 family members of the patients discharged from intensive care units participated in the survey by convenience sampling method. A questionnaire of sociodemographic information and a researcher-made questionnaire on the educational needs of the family of patients discharged from the postintensive care units were used for data collection. Results. The mean total score of the educational needs of the patients’ families was 31.81 and 35.33 from views of families and nurses, respectively. Nurses significantly estimated the educational needs of families more than what they did (P<0.001). The families and nurses reported the educational needs of self-care as well as nutrition and medicine at the highest level, respectively. Both groups reported the educational needs of defecation at the lowest level. Nurses estimated higher educational needs in all dimensions, except for the patient’s mental health and family self-care than families (P<0.001). Conclusion. According to the present study, the educational needs were high from the views of nurses and families. Family need assessment is essential in designing and applying instructional interventions. Given the high level of family needs, implementing educational and practical interventions is necessary to enhance their skills.